1974
DOI: 10.1002/1097-0142(197412)34:6<1992::aid-cncr2820340618>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Is subependymoma (subependymal glomerate astrocytoma) an astrocytoma or ependymoma?:A comparative ultrastructural and tissue culture study

Abstract: A fourth ventricle lesion containing both areas of typical ependymoma and subependymoma has been studied with the electron microscope. Both foci show ependymal and astrocytic elements. In the subependymoma, a larger number of astrocytes, more frequent cytoplasmic degeneration, and increased glial filaments in the ependymal cells are found. These cellular changes in the subependymoma yield a distinctive light microscopic appearance. However, at the ultrastructural level, the similarity of cellular components, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…However, recent several studies of the in vitro culture showed dual differentiation into glial and neuronal cells [2,3,12,13,15,[17][18][19][20][21]. Our recent in vitro culture study (data was not shown here) also showed similar results.…”
Section: Hypothesis For the Tumor Originsupporting
confidence: 82%
See 2 more Smart Citations
“…However, recent several studies of the in vitro culture showed dual differentiation into glial and neuronal cells [2,3,12,13,15,[17][18][19][20][21]. Our recent in vitro culture study (data was not shown here) also showed similar results.…”
Section: Hypothesis For the Tumor Originsupporting
confidence: 82%
“…Subependymal glia such as astrocytes or ependymal cells was considered as a possible tumor origin. Otherwise it has been suggested that it is a kind of hamartoma [7,15]. SEGAs are often observed in tuberous sclerosis and usually occur at lateral ventricle around foramen of Monro [3,15].…”
Section: Characteristics Of Tumors Located Around Foramen Of Monromentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, subependymomas are likely to be a variant of ependymomas and the astrocytic component represented reactive astrocytic cells. 7) Electron microscopy of four cases of fourth ventricular subependymomas found cells similar to the ependymal glial precursor cells seen in adult subependymal cell layers, 15) suggesting that subependymomas are a separate entity from ependymomas and astrocytomas, probably arising from ependymal glial cells in the subependymal cell layers. Tanycytes were first identified as cells in the subependymal zone of the elasmobranch, the processes of which spanned the brain from the pial to the ventricular surface.…”
Section: Discussionmentioning
confidence: 99%
“…3,16,17 Ependymal glial precursor cells are bipotential cells, with the ability to differentiate into either an ependymal cell or an astrocyte. Among 43 subependymoma cases, we found 8 cases with mixed ependymoma, and 1 with mixed astrocytoma.…”
Section: Lower Incidence Of Intracranial Subependymoma and Its Relatimentioning
confidence: 99%